Evaluation of Safety and Cost-Effectiveness of the Low Risk Ankle Rule in One of Europe's Busiest Pediatric Emergency Departments. Issue 10 (October 2015) - Ramasubbu, Benjamin; McNamara, Roisin; Okafor, Ike; Deiratany, Samir
Abstract : Objectives: LowRisk Ankle Rule (LRAR) has 100% sensitivity for identifying clinically important pediatric ankle fractures (high-risk injuries) and has the potential to safely reduce imaging by approximately 60%. This study investigates the safety and cost-effectiveness of this rule in our institution. Methods: All patients triaged during July and August 2013 with an "ankle injury" had a retrospective clinical notes and radiology report review. Data were recorded using Excel and tests of significance, χ 2 test. Results: One hundred twenty-one patients were included. Of these, 65 were female and 56 were male (no significant difference in sex, P = 0.41). Mean age was 9.95 years. Seventy-eight (64%) had LRAR positive examinations. Of these, 77 (98.7%) had an x-ray and 12 (15%) had fractures. Of those with fractures, none had high-risk injuries. Eighteen (100%) of the doctors in our ED felt that a clinical decision rule would be of use within the department. Only 8 (44%) had heard of the LRAR, and of these, only 4 (50%) would be confident to implement the LRAR. Forty-four (88%) of parents felt that an x-ray is required in the diagnosis of ankle injuries in children, and 41 (82%) would want to know whether their child had an ankle sprain or a low-risk fracture even if the management was not different. Conclusions: By implementing the LRAR in our institution, we could reduce ankle x-rays by 64%. This would offer a significant reduction in radiation exposure to a radiosensitive population. Estimated costs of an ankle x-ray and interpretation are [Euro sign]47 (65), thus with more than 800 carried out per year in The Children's University Hospital, a potential annual saving is [Euro sign]25, 000 (34, 500).